Fundamentals of HR Analytics : a Manual on Becoming HR Analytical. - Diez, Fermin (Emerald Publishing Limited, 2019)
Providing practical, hands-on approaches to connect data to HR policies and practices to help influence overall business performance, this book is an essential resource for aspiring, new and experienced HR professionals across a wide range of industrial contexts.